Three widely used pesticides and their mixtures induced cytotoxicity and apoptosis through the ROS-related caspase pathway in HepG2 cells. (June 2021) - Wang, Tiancai; Ma, Mengmeng; Chen, Chen; Yang, Xi; Qian, Yongzhong
Abstract: Difenoconazole, cypermethrin and triazophos are widely used pesticides in agricultural production and frequently detected in foods. The aim of this study was to determine the effect of these pesticides and their mixtures on cell viability, reactive oxygen species (ROS), lactate dehydrogenase (LDH) content, apoptosis rate and DNA fragmentation and synthesis in human hepatocellular carcinoma cells (HepG2). The order of inhibitory effects for the individual pesticides was ranked as difenoconazole > cypermethrin > triazophos. The enhanced expression of caspase-3, caspase-7 and PARP activity was observed in HepG2 cells, which was 1.7, 1.3 and 1.6-fold higher than the control, respectively, along with significant protein cleavage; and induced apoptosis in a concentration-dependent manner. Further, the pesticide mixtures significantly increased ROS level (up to 1.3-fold), induced DNA fragmentation (up to 1.8-fold), inhibited DNA synthesis (up to 53%), and damaged the cells by destroying the cell membrane and producing a large amount of LDH at concentration range of 10–30 μM. Specifically, mixtures containing difenoconazole showed stronger toxicities than individual pesticides, implying higher health risks associated with mixtures. Our results show that three widely used pesticides exhibited cytotoxicity and apoptosis through the ROS-related caspase pathway, providing a basis for evaluation of health risks from pesticide mixtures via food consumption. Graphical abstract: Image 1 Highlights: Cytotoxicity of three widely used pesticides and their mixtures was evaluated. Expression of caspase-3, caspase-7 and PARP activity was enhanced in HepG2 cells. Pesticide mixtures increased ROS and LDH level, inhibited DNA synthesis, and damaged cells. Pesticide–induced apoptosis was identified through the ROS-related caspase pathway.